The House I'd Like to Have: Women's Spatial Cultures, Design, and Aesthetic in 20th Century Italy - Forlini, Francesca Romana (Interiority, 2024)
"Has any woman ever designed architectures in the past centuries? You may ask her to design a hut, not even a temple! She can't. She is foreign to architecture." These infamous words of Benito Mussolini (1927) reflected the widespread sexism of the Fascist regime and prompted a silent wave of dissent pioneered by women intellectuals, architects, writers, and journalists in the early 20th century. They advocated for a valuable feminine contribution to Italian architecture and their story is still partially unknown by architectural historians today. This essay tackles Italian women's spatial design and aesthetics during the regime, a period in which they kept silently operating within the built environment as professional architects with unbuilt projects and as amateur designers inside their homes. These circumstances, as argued here, determined the emergence of a feminine and feminist approach to architectural design and criticism that transcended the male boundaries of high culture, reinforced by the Fascist regime and in line with the modernist binary understanding of taste and cultural architectural production. The latter is studied through the lens of cultural domesticity, a theoretical framework that merges cultural sociology, feminism, and architecture. By focusing on Italian women's lived experiences and unconventional design approaches, this study ultimately looks at the consolidation of feminine aesthetics and how it informed women's spatial design as it keeps challenging the boundaries of architectural history.